Persentase keberhasilan inseminasi buatan dosis ganda pada sapi persilangan Limousin dengan karakter lendir serviks yang berbeda - Nurul Layla; Yadi Malda; Aulia Puspita Anugra Yekti; Asri Nurul Huda; Rizki Prafitri; Kuswati Kuswati; Trinil Susilawati (Livestock and Animal Research, 2022)
Objective: The aim of the study was to find out the successful pregnancy in Limousin crossbreed cattle using double-dose AI method on different characters of cervical mucus.Methods: The material used in this study were 45 female cattle with BCS criteria 3-6 on a scale of 1-9 and aged 1.8-6 years. The parameters observed were the condition of the mucus, the pH of the mucus and the electrical resistance of the mucus. AI method uses a double dose method with 4+ semen deposition (cornua utery).Results: The results showed that the highest percentages of NRR 1 and NRR 2 were shown by cattle with the criteria for mucus conditions being present and abundant. It has a pH value of 8 and an electric current resistance is in the range of 20-29 Ω with a percentage of NRR 1 of 62.22%, 53.33% and 71.11%, while the NRR 2 has a percentage of respectively 60.00%, 51.11% and 68.89%. The highest percentage of CR was also shown by cattle with the mucus character, which had percentages of 33.33%, 33.33% and 42.22%, respectively.Conclusions: It was concluded that the highest percentage of pregnancy was shown by cattle with the criteria of mucus being present and abundant, having a pH value of 8 and having an electric current resistance value in the 20-29 Ω category.